INVESTIGATION OF QUALITY OF HOT-ROLLED ROUND BAR OF STEEL OF GRADE 42CRMOS4 NOT SUBJECTED TO TO ANTIFLAKE PROCESSING IN WELL OF SLOW COOLING OF MILL 850 RUP «BMZ» FOR COMPLIANCE WITH REQUIREMENTS OF ND BY MICROSTRUCTURE - V. A. Politov; L. A. Drobyshevskiy (Литьë и металлургия)
The quality of the hot-rolled round rolling of steel of grade 42CrMoS4, not subjected to antiflake processing in well of slow cooling of mill 850 RUP «BMZ» is studied.